COVID-19 Pandemic Stress-Induced Somatization in Transplant Waiting List Patients - Wagner-Skacel, Jolana; Dalkner, Nina; Bengesser, Susanne; Ratzenhofer, Michaela; Fink, Nadja; Kahn, Judith; Pilz, Rene; Mörkl, Sabrina; Lenger, Melanie; Fazekas, Christian; Matzer, Franziska; Butler, Mary; et al. (Frontiers in Psychiatry, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has resulted in widespread socioeconomic restrictions including quarantine, social distancing and self-isolation. This is the first study investigating the psychological impact of the pandemic on patients waiting for liver or kidney transplantation, a particularly vulnerable group. Methods: Twenty-seven patients on the transplantation waiting list and 43 healthy controls took part in an online survey including the Beck Depression Inventory (BDI-2), the Brief Symptom Inventory-18 (BSI-18), the Pittsburgh Sleep Quality Index (PSQI), the Alcohol Use Identification Test (AUDIT-C), the 12-item Operationalized Psychodynamic Diagnosis Structure Questionnaire (OPD-SQS) and a questionnaire to determine cognitions and beliefs, attitude and fear related to COVID-19. Results: BSI-18 Somatization was increased in waiting list patients compared to controls. Correlation analyses indicated a relationship between Somatization and the fear of contracting the coronavirus in the patient group; however this association was weak. In patients and controls, other psychologicial symptoms (depression, anxiety) correlated highly with emotional distress due to social distancing. There were no differences between patients and controls in depression scores and sleep disturbances. Alcohol consumption and personality structure were not related to COVID-19 fears. Conclusion: In times of the first lockdown during the COVID-19 pandemic, patients on the transplantation waiting list have high somatization symptoms associated with COVID-19 fears. As vulnerable group, they need psychological counselling to improve mental well-being during times of crisis.